Ethyl acetate produced by Hanseniaspora uvarum is a potential biocontrol agent against tomato fruit rot caused by Phytophthora nicotianae - Liu, Ziyu; Tian, Junjie; Yan, Hao; Li, Delong; Wang, Xue; Liang, Wenxing; Wang, Guangyuan (Frontiers in Microbiology, 2022)
In this study, an oomycete strain FQ01 of Phytophthora nicotianae, which could cause destructive postharvest disease, was isolated. At present, chemical fungicides are the main reagents used for controlling Phytophthora diseases. It is necessary to find new control techniques that are environmentally friendly. The biocontrol activity of Hanseniaspora uvarum MP1861 against P. nicotianae FQ01 was therefore investigated. Our results revealed that the volatile organic compounds (VOCs) released by the yeast strain MP1861 could inhibit the development of P. nicotianae FQ01. The major component of the VOCs produced by the yeast strain MP1861 was identified to be ethyl acetate (70.8 %). Biocontrol experiments showed that Phytophthora disease in tomato fruit could be reduced by 95.8 % after the yeast VOCs treatment. Furthermore, ethyl acetate inhibited the mycelial growth of the oomycete strain FQ01, and damaged the pathogen cell membrane. This paper describes the pioneering utilization of the yeast strain MP1861 for biocontrol of postharvest fruit rot in tomato caused by P. nicotianae.